An Ecosystem: Seeing via the Buddhist Theory of Dependent Co-Arising - Somaratne, G.A. (Journal of International Buddhist Studies, 2015)
The theory of dependent co-arising has this quality and can be applied in understanding the world, our present environment, as an ecosystem. Human beings lived in harmonious with nature. They dwelled in forest, caves and places endowed with natural water sources. They drew on their environment for their basic needs in food, clothing, shelter and medicine. Most of their tools were made roughly and simply from stone or wood. They did not have machinery and modern equipment to ease their day-to-day living. Therefore natural resources were, by and large, left to prosper and flourish as men had not yet learned to capitalize on them. Modern science and technology is very efficient tool for bringing about development to the world, it is neutral by nature and it must be utilized and controlled by a mature person, fully developed physically and spiritually. Buddhism views man a part of nature. If nature is destroyed man cannot live. By abusing nature, man abuses himself. Therefore, Buddhist ethics would follow from the basic understanding of nature. Only if we agree on this common ground, can we proceed to save the world.